From confinement to containment : Japanese/American arts during the early Cold War - Tang, Edward (Asian American history and culture, 2019)
"From Confinement to Containment examines four Japanese and Japanese American artists--the novelist Hanama Tasaki, the actor Yamaguchi Yoshiko, the painter Henry Sugimoto, and the children's author Yoshiko Uchida--whose lives and work explored overlapping transpacific legacies of immigration, imperialism, confinement, and global conflict in U.S.-Japan relations"--